Factors Affecting Interest To Work In A Public Accounting Firm: A Study Of Internship Students - Gusti Ayu Made Denisa Ari Putri; Komang Ayu Krisnadewi (SEAN Institute, 2024)
According to data from the Center for the Accountant Profession, the Public Accountant profession experienced a low increase, while public companies listed on the IDX experienced a high increase. So there is a gap in numbers between providers of public accounting services and service users, namely public companies which require an opinion from the services of a public accounting firm (KAP) on the fairness of their financial reports. This research aims to determine the effect of variations in assignments, workload, work challenges and superior support in student internship programs on interest in working at KAP. Research on 120 respondents who had interned at a Public Accounting Firm was taken using a purposive sampling technique (snowball sampling technique). Methods of data analysis using the validity and reliability of the questionnaire, multiple regression. The results of the analysis show that variations in tasks, workload, work challenges, and superior support have a positive influence on interest in working in a public accounting firm, while workload has a negative influence on interest in working in a public accounting firm. However, simultaneously all independent variables influence the dependent variable. The results of the coefficient of determination of 0.505 indicate that the independent variable is able to influence the dependent variable by 51% and the remaining 49% is influenced by variables outside this research.